Modeling Satellite Gravity Gradient Data to Derive Density, Temperature, and Viscosity Structure of the Antarctic Lithosphere - Pappa, F. (author); Ebbing, J. (author); Ferraccioli, F. (author); van der Wal, W. (author) (Journal of Geophysical Research: Solid Earth, 2019)
In this study we combine seismological and petrological models with satellite gravity gradient data to obtain the thermal and compositional structure of the Antarctic lithosphere. Our results indicate that Antarctica is largely in isostatic equilibrium, although notable anomalies exist. A new Antarctic Moho depth map is derived that fits the satellite gravity gradient anomaly field and is in good agreement with independent seismic estimates. It exhibits detailed crustal thickness variations also in areas of East Antarctica that are poorly explored due to sparse seismic station coverage. The thickness of the lithosphere in our model is in general agreement with seismological estimates, confirming the marked contrast between West Antarctica (<100 km) and East Antarctica (up to 260 km). Finally, we assess the implications of the temperature distribution in our model for mantle viscosities and glacial isostatic adjustment. The upper mantle temperatures we model are lower than obtained from previous seismic velocity studies. This results in higher estimated viscosities underneath West Antarctica. When combined with present-day uplift rates from GPS, a bulk dry upper mantle rheology appears permissible. Astrodynamics & Space Missions